Impact of small-scale irrigation schemes on farmers livelihood, the case of Mekdela Woreda, North-East Ethiopia - Eliyas Assefa; Zemen Ayalew; Hawlet Mohammed (Cogent Economics & Finance)
Small scale irrigation has multi-dimensional effects on the livelihood development of the rural people in Ethiopia. Thus, the main objective of this study was to examine the impact of small-scale irrigation on farmers’ livelihood. A stratified random sampling technique was applied to select 96 users and 162 non-user sample respondents. The collected data were analyzed using descriptive statistics and an econometric model. Binary logit and Endogenous switching regressions model were employed to identify the determinant of small-scale irrigation participation and its impact on farmers’ livelihood respectively. The Binary logit model result indicates that age and age square of the household, own cultivated land, off-farm job participation, extension contact, distance from homestead to a nearly local market, distance from home to the scheme, and having irrigation user neighbor are significant factors affect farmers’ decision to practice irrigation. To capture the impact of irrigation on farmers’ livelihood, the total income of the household was used in the endogenous switching regression model. The model result shows that the positive and significant impact of irrigation schemes had increased users’ total income by 7829 ETB (8.5%), as compared to non-users. This shows how significant the role of a small-scale irrigation scheme in improving the livelihood condition of farmers in the study area. The finding of this study shows that improving access to market and water for irrigation, provision of extension, and other complementary services would increase the participation of irrigation and improve livelihood.